Apoptosis signal-regulating kinase 1 (ASK1) is linked to neural stem cell differentiation after ischemic brain injury - Song, Juhyun (Nature Publishing Group, 2013)
Neural stem cells (NSCs) have been suggested as a groundbreaking solution for stroke patients because they have the potential for self-renewal and differentiation into neurons. The differentiation of NSCs into neurons is integral for increasing the therapeutic efficiency of NSCs during inflammation. Apoptosis signal-regulating kinase 1 (ASK1) is preferentially activated by oxidative stress and inflammation, which is the fundamental pathology of brain damage in stroke. ASK1 may be involved in the early inflammation response after stroke and may be related to the differentiation of NSCs because of the relationship between ASK1 and the p38 mitogen-activated protein kinase pathway. Therefore, we investigated whether ASK1 is linked to the differentiation of NSCs under the context of inflammation. On the basis of the results of a microarray analysis, we performed the following experiments: western blot analysis to confirm ASK1, DCX, MAP2, phospho-p38 expression; fluorescence-activated cell sorting assay to estimate cell death; and immunocytochemistry to visualize and confirm the differentiation of cells in brain tissue. Neurosphere size and cell survival were highly maintained in ASK1-suppressed, lipopolysaccharide (LPS)-treated brains compared with only LPS-treated brains. The number of positive cells for MAP2, a neuronal marker, was lower in the ASK1-suppressed group than in the control group. According to our microarray data, phospho-p38 expression was inversely linked to ASK1 suppression, and our immunohistochemistry data showed that slight upregulation of ASK1 by LPS promoted the differentiation of endogenous, neuronal stem cells into neurons, but highly increased ASK1 levels after cerebral ischemic damage led to high levels of cell death. We conclude that ASK1 is regulated in response to the early inflammation phase and regulates the differentiation of NSCs after inflammatory-inducing events, such as ischemic stroke.